Analisis Bibliometrik Tentang Perkembangan Penelitian Debt Covenant - Nugroho, Ario Bagus; Ermayanti, Dian; Ervina, Ervina; Putra, Rakmat Dwi Anugrah; Riyadi, Slamet; Pandin, Maria Yovita R. (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The amount of research done by researchers would make finding information a piece of cake, for the last 10 years (2013-2024) research about debt covenants were considered adequate for management to help fix the company’s accounting management problems. But there’s still quite a lot of things circling the debt covenant that were still untouched that could fix and could also worsen the company’s situation. This study tried to dig deep into the connections that occurred based on the previous research by using two steps which was the use of Publish or perish software to find publications data and the use of VOSviewer software to cluster and visualize those publications data. The results of this research were items of research like firm value on a yellow cluster didn’t have any connection on a blue cluster’s items of research but has connections with the red cluster which was debt covenant violation and the items of research debt contract on a green cluster. The other result was there were items of research like firm value and audit quality that were studied rarely also their average of publication years were quite new. These things could support those items of research to become the new indicators for future research on debt covenant.